Relação entre o envelhecimento de machos e fêmeas de Drosophila melanogaster com a Ferroptose - Gomes, Karen Kich (2024)
The aging process is inevitable in the life of living organisms. This process is characterized by a functional decline in physiological and behavioral functions, resulting in frailty, diseases, and eventual death. Over the last few decades, interest in aging has significantly grown, partly due to the fact that the elderly have become a larger portion of the population, resulting in increased healthcare expenditures by nations. Harman, in his free radical theory (1950), outlined the fundamental mechanism of aging because of the accumulation of reactive oxygen species (ROS) originating from cellular metabolism and a reduction in life expectancy. Recent research indicates that other processes, such as the accumulation of iron (Fe), play a crucial role in promoting aging. Fe is an essential micronutrient in the life of living organisms, participating in biological processes such as cellular respiration, energy production, DNA synthesis, ecdysone, and lipid and dopamine metabolism. Alterations in its regulatory mechanism, resulting in accumulation or deficiency, can be detrimental to the organism. The accumulation of labile iron can lead to a form of cell death known as ferroptosis. Ferroptosis, a form of iron-dependent cell death, involves stages such as glutathione (GSH) and/or glutathione peroxidase 4 (GPx4) depletion, increased intracellular iron, and excessive (ROS). Reproduction, and lipid peroxidation. This specific type of cell death has been associated with the pathogenesis of various disorders, encompassing conditions ranging from cardiovascular diseases to neurological disorders. The increasing understanding of how ferroptosis plays a central role in different pathological contexts highlights its complexity and importance in a variety of medical conditions. This study investigated behavioral and oxidative stress parameters during the aging process of male and female Drosophila melanogaster, indicating, in conjunction with elevated iron levels, the presence of ferroptosis. Our results revealed that older flies (30 days old) of both sexes exhibited impaired locomotion and balance compared to younger flies (5 days old). We also observed that older flies produced higher levels of ROS, a decrease in GSH levels, and an increase in lipid peroxidation. In parallel, Fe levels were elevated in the hemolymph of the flies. Depletion of GSH with diethyl maleate (DEM) potentiated age-associated behavioral impairments. Our data revealed biochemical effects characteristic of ferroptosis occurrence during the aging of Drosophila melanogaster, emphasizing the involvement of GSH in age-related damage, partially attributed to elevated Fe levels. The current study enhances our understanding of the biochemical events involved in the aging process and contributes to the development of new therapeutic approaches aimed at improving the quality of life for the elderly.